-2q-17=15-3q

Simple and best practice solution for -2q-17=15-3q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2q-17=15-3q equation:



-2q-17=15-3q
We move all terms to the left:
-2q-17-(15-3q)=0
We add all the numbers together, and all the variables
-2q-(-3q+15)-17=0
We get rid of parentheses
-2q+3q-15-17=0
We add all the numbers together, and all the variables
q-32=0
We move all terms containing q to the left, all other terms to the right
q=32

See similar equations:

| 6w=-39 | | -13n-8n+5n+19n+11n-5=-19 | | 3−2x=√2x+3 | | 3780=180(n-2) | | (4x+4)=(2x+11) | | 11/12-r=8/12 | | 8b+-7b-2=-16 | | P2-16b=12 | | 5(2p–7)=16 | | A/z=18 | | x-(x-2)/(2)+(1)/(7)=(5x)/(14) | | 78÷n=13=n=5 | | -(t/12)=(1/4) | | 3=-2y+7 | | 8x+14=7x+6 | | 5q-4q+q-1=19 | | 9x-20=0 | | -t/12=1/4 | | 4(2y-1)=-12 | | 78÷n=13n=5 | | 3a-a-a+1=18 | | 10z+3z+z-7z-5z=12 | | -5g+-3g+7g+9g-20g=-12 | | 75÷y=5=15 | | -15=-5(3x-6) | | −3a+43=2(−32a+2)-3a+43=2-32a+2 | | 75÷y=5y=15 | | (2/3)x-12=-x-13 | | 24x+32=8x+40 | | 1t+-18=-4 | | 10q+60=5q | | (4x9)=(4x8) |

Equations solver categories